FEEDBACK IN THE LEARNING PROCESS OF THE MATH "LEVEL 0" COURSE - de la Cruz Sánchez, Alejandro Walter (2007)
We show the results of the teaching-learning experience of the Math 'Level 0' course given to the freshers at UPC who do not pass the Math 'Level Exam'. The work was based on the feedback of the learning process and it was done at the same time that the university 'methodology of competencies' was being applied. The difference was based on the feedback given on each class based on evaluations that measured their cognitive and 'procedural knowledge'(part calculus and modelling of everyday situations). The comparison with the results obtained at the end of the week in general evaluations (common for each class) were positive, which encouraged us to keep up this learning process by common agreement.At the end of the course when comparisons between each class were made we saw that 70% passed the course due to applying this methodology. The interviews with the students showed that there was general satisfaction with the learning process as well as the knowledge obtained throughout the semester. Nevertheless students commented that one of the main problems was timeplanning inside and outside of the classroom. Unexpectedly the empathy developed with the students produced a synergy that might be worth studying.